Identification of Factors Contributed to Beef Cattle Reproductive Disorders in Ogan Komering Ulu Timur Regency (OKU Timur) of South Sumatra Province in UPSUS SIWAB Program 2018 - Armelia, Vony; Saleh, Dadang Mulyadi; Setianto, Novie Andri (ANIMAL PRODUCTION, 2018)
The research entitled â€œIdentification of Factors Contributed toÂ  Beef Cattle Reproductive Disorders in Ogan Komering Ulu Timur Regency (OKU Timur) of South Sumatra Province in UPSUS SIWAB Program 2018â€ was done on Semendawai Suku III and Semendawai Timur, OKU Timur regency, South Sumatra on October 10th until November 10th 2018. The purpose of this research is to identify the factors contributed to reproductive disorders of beef cattle, mapping the factors that affect reproductive disorders of beef cattle and generate strategies to improve reproductive performance of beef cattle in OKU Timur Regency. The targets in the study are 40 beef cattle breeders, 2 inseminators and 2 employees of the Local Office of Fisheries and Livestock Services of OKU Timur Regency.The research was done by survey, the method used was qualitative modeling with the Causal Loop Diagram (CLD). The variables observed in the study were variables related to reproductive performance consisted of Body Condition Score (BCS), Calving Interval (CI), Service per Conception (S/C), Conception Rate (CR) and variables related to factors indicated to have contribution to reproductive disorders such as farmer characteristics, resources owned by farmers and resources possessed by inseminators. The results showed that reproductive disorders of beef cattle in OKU Timur Regency included ovarian hypofunction, endometritis, pyometra, systolic ovary, silent heat, vulvitis, vaginitis, mummification and placental retention. The identified factors contributed to reproductive disorders are low quality and availability of feed, low breeders' knowledge, absence of postpartum treatment, limited medical supplies and quantity, unstandard technical implementation of artificial insemination, cross breeding of heifer, insufficient inseminator facilities. Strategies that can be done to improve the reproductive performance of beef cattle is to increase the role of the government in providing superior feed seeds and assisting by Universities; increasing the number of medicalsupplies and facilities, equip inseminator with sufficient facilities, and technical insemination and increasing the intensity of extension services to improve farmers' knowledge and utilization of potential agricultural waste with technology.